Рефлексивність як психологічна умова гармонізації особистісного розвитку курсанта ВНЗ МВС - Жданова, І. В.; Ластовець, І. В.; Zhdanova, I. V.; Lastovets, I. V. (Право і безпека. - 2015. - № 1 (56). - С. 96–101., 2015)
Розкрито поняття гармонійний» та «дисгармонійний розвиток», «гармонізація», «рефлексія». Визначено психологічні умови гармонізації особистісного розвитку курсантів ВНЗ МВС, якими стали мотивація до гармонійного розвитку, суб’єктність особистості, рефлексивність особистості курсанта. Розкрито сутність і психологічний зміст рефлексивності як психологічної умови гармонізації особистісного розвитку курсанта ВНЗ МВС.

The article is devoted to the psychological analysis of reflexivity as psychological condition to harmonize personal development of a cadet of a higher educational establishment of the Ministry of Internal Affairs (hereinafter – Universities of the MIA). Based on the analysis of scientific psychological literature the essence of the concepts «harmonic» and «disharmonious development», «harmonization» are revealed; specific features of the social situation of the future law enforcement officer’s personal development in terms of departmental University are determined. The necessity to harmonize the personal development of cadets of the Universities of the MIA and the scientific search of psychological conditions are grounded. By the assistance of correlation and factor analysis the authors identify psychological conditions to harmonize personal development of cadets of the Universities of the MIA, which are motivation to the harmonious development, individual’s subjectivity, personality’s reflexivity. Based on modern psychological research the authors reveal the content of the concept «reflection»; define and ground psychological essence of reflexivity as psychological condition to harmonize personal development of a cadet of the Universities of the MIA. It is shown that reflexivity of cadets of the Universities of the MIA consists of sensitivity to the «I», self-understanding, autosympathy, positive attitude towards themselves, emotional balance and prudence, ability for psychological proximity to people, internality in the sphere of interpersonal relations, insight. Based on the obtained results the authors have elaborated practical recommendations to harmonize personal development of cadets of the Universities of the MIA, the essence of which is the actualization of psychological conditions for the harmonious development of cadets. Actualization of reflexivity as a psychological condition of harmonization involves the development of positive self-concept, selfunderstanding, self-acceptance, socio-psychological mechanisms of understanding the others among cadets.

Раскрыты понятия «гармоничное» и «дисгармоничное развитие», «гармонизация», «рефлексия». Определены психологические условия гармонизации личностного развития курсантов вузов МВД, которыми стали мотивация к гармоничному развитию, субъектность личности, рефлексивность личности курсанта. Раскрыты сущность и психологическое содержание рефлексивности как условия психологической гармонизации личностного развития курсанта вузов МВД.
Zhdanova, I.V. and Lastovets. I.V. (2015), “Reflexivity as a psychological condition to harmonize personal development of a cadet of a higher educational establishment within the Ministry of Internal Affairs” [“Refleksyvnist yak psykholohichna umova harmonizatsii osobystisnoho rozvytku kursanta VNZ MVS”], Pravo i Bezpeka, No. 1, pp. 96–101 .
Жданова, І. В. Рефлексивність як психологічна умова гармонізації особистісного розвитку курсанта ВНЗ МВС / І. В. Жданова, І. В. Ластовець // Право і безпека. - 2015. - № 1 (56). - С. 96–101.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; гармонійний розвиток особистості; harmonious development; гармоничное развитие личности; психологічні умови гармонізації особистості; гармонійна особистість; курсант вищого навчального закладу; рефлексивність; psychological conditions of harmonization; harmonious personality; cadets of a higher educational establishment; reflexivity; психологические условия гармонизации личности; гармоничная личность; курсант высшего учебного заведения; рефлексивность